PENGARUH RELIGIUSITAS, NORMA SUBJEKTIF, DAN PERCEIVED BEHAVIORAL CONTROL TERHADAP NIAT BELI MAKANAN BERLABEL HALAL (Studi Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2016 ) - Agus Mukorobin; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to determine the effect of religiosity on food purchase intentions with halal label, the influence of subjective norms on food purchase intentions labeled with halal, and the effect of perceived behavioral control on food purchase intentions with halal label. This research is an explanatory research type. The subjects of the study were 85 students of FEB Islamic University of Malang. Data collection method is done by using a questionnaire. The analytical method used is the validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination test, and hypothesis testing. The results showed that religiosity affects the purchase intention of halal-labeled food, subjective norms do not affect the intention to buy food labeled as halal, and perceived behavioral control influences the purchase intention of halal labeled food.Keywords: religiosity, subjective norms, perceived behavioral control, intention to buy food labeled as halal.